Efficacy of Anger Management Skills on Reducing Aggression and Improving Adjustment in Addicts Treating with Methadone in Sari-Iran - Shahnam Abolghasemi (Journal of Global Pharma Technology, 2017)
Background: Aggression and lack of adjustment are important issues in incidence and recurrence of addiction. This study aimed to evaluate the effectiveness of anger management skills training on modifying these variables among addicts treating with methadone. Methods: In the present experimental study all patients referred to four private addiction treatment centers supported by Sari University of Medical Sciences in north of Iran in 2015, to receive methadone treatment, completed Bell Adjustment Questionnaire and Buss-Perry Aggression Questionnaire. Sixty-four men scored high on aggression questionnaire and low on the Bell were identified. Among them forty were selected randomly and were replaced in two groups (twenty in case groups and twenty in control group). Nine sessions anger management skills training was performed in case group and both groups completed questionnaire again. Data were analyzed using covariance in SPSS-20.Findings: Training anger management skills reduced aggression and increased personal and social adjustment among addicts treating with methadone, significantly (p<0.001).Conclusion: Given the benefits of anger management skills as a non-pharmacological and effective approach, using this strategy as a part of a comprehensive treatment for addicts recommended.Keywords: Anger management therapy, Aggression, Personal-social adjustment, Methadone, Drug users.